Application of Biomechanical Analysis of Pencak Silat Techniques - Alan Alfiansyah Putra Karo Karo; Tandiyo Rahayu; Heny Setyawati; Siti Baitul Mukarromah (International Conference on Science, Education, and Technology, 2023)
Pencak silat is a self-defense method with distinctive movements that utilize every part of the human body as a sport. These movements are organized into a set of fundamental techniques, including as blocks, punches, kicks, kicks, punches, drops, and slams, and are known as moves. Based on the foregoing, the researchers' plan for this study is to do biomechanical analyses of the Pencak Silat technique. The method used in this research is scientific journals are reviewed quantitatively in order to provide an overview of the journals' quality, maturity, productivity, and other factors. Journals or scientific publications published between 2019 and 2023 that were retrieved from the Scopus and Sinta databases served as the research data for this study. Using "pencak silat biomechanics analysis" as a keyword in Google Scholar, search for published articles using that phrase. When a research paper meets the criteria, it is gathered, and a summary of the journal is created including the author's name, the year, the topic, the sample, the methodology, and a description of the results or findings. The results of an application of biomechanical analysis of pencak silat techniques by searching literature related to the analysis of pencak silat biomechanics, it can be concluded that the biomechanical analysis that can be applied to pencak silat techniques is time, angles, direction, flexion, extension, rotation, adduction, visual focus, force, moment of inertia, rotational kinetic energy, effort.